Investigation of phase state and heat storage form of the phase change material (PCM) layer integrated into the exterior walls of the residential-apartment during heating season. (15th September 2020) - Pirasaci, Tolga
Abstract: This paper presents a study on the integration of PCM layer to the exterior walls of a residential building. The main aim of the paper is to investigate the phase state and the heat storage form of a PCM layer integrated into the exterior walls of a residential apartment during heating season. In addition, the winter thermal performance and winter energy saving potential of a residential apartment incorporated with a PCM layer is presented. In the study, a numerical model including building characteristics, residents' behavior and outdoor conditions was created and validated with the experimental data in the literature. Numerical simulations have been performed for different types of wall structure under changing weather conditions. From the obtained results it can be seen that PCM layer integration give better results for the cases where there is no phase change. Although winter heating energy requirement is reduced with PCM layer integration, it is concluded that PCM layer integration is not suitable since PCM usage is unreasonable in cases where there is no phase change. Highlights: The appropriateness of PCM integration was questioned to reduce heating energy. Numerical model for the residences in Ankara (cold snowy winters) was created. Winter heating energy requirement was reduced with PCM layer integration. PCM layer integration gave better results where there was no phase change. PCM layer integration found to be not suitable since there was no phase change.